Quality of sleep and physical health issues in patients suffering from psychiatric disorders - Afzal, Samreen; Siddique, Irun; Dogar, Imtiaz Ahmad; Zareen, Gull; Khawaja, Imran; Azeem, Muhammad Waqar; Haider, Nighat (Journal of Pakistan Psychiatric Society, 2019)
ABSTRACT